Evaluation of Morphology and Prevalence of Palatoradicular Grooves on Affected Maxillary Anterior Teeth Using Cone-Beam Computed Tomography: An Institutional Retrospective Study - Dilara Baştuğ; Leyla Benan Ayrancı (Applied Sciences)
This retrospective study aimed to evaluate the prevalence, morphological types, and distribution patterns of palatoradicular grooves (PRGs) in maxillary anterior teeth using cone-beam computed tomography (CBCT) in a Turkish population. CBCT images of 1553 patients from the radiology archive of Ordu University Faculty of Dentistry (2021–2022) were reviewed. A total of 920 patients (4012 teeth) met the inclusion criteria. The presence, type, and localization of PRGs were assessed. Groove types were classified as Type 1, 2, 3A, or 3B; localization was recorded as mesial, distal, or midpalatal. Bilateral and unilateral occurrences were also analyzed. Statistical analysis involved chi-square tests, Tukey’s HSD, and Cohen’s kappa for intra-observer reliability. PRGs were detected in 23.6% of patients and 10.42% of teeth. Lateral incisors were most affected (87.56%). Type 1 grooves were most common (71.53%), with midpalatal localization being most frequent (54.07%). Bilateral grooves were significantly more prevalent than unilateral ones (p < 0.001). No significant association was found between groove type and tooth type or between gender and bilaterality. This study revealed a high prevalence of PRGs, especially in maxillary lateral incisors, with a significant tendency toward bilateral and midpalatal presentation. CBCT proved essential for detecting palatoradicular grooves, aiding diagnosis and treatment.